The American Broadcast My Lobotomy as an Example of a Radio Feature in the West - Kowalska, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article consists of two parts. In the first one, I analyse relations between a reportage and a feature. Differences can be found in the way these notions are defined by scholars in Poland and in Western Europe. Polish radio documentaries are based on authenticity, while in a feature the truth intermingles with fiction. My Lobotomy, by David Isay and Piya Kochhar, serves as an example of a work which presents both authentic characters and some fictional elements. In the second part of the article I focused on the analysis of this American feature. As far as I am concerned, what makes the work most interesting is the relationship between the protagonist’s authentic and spontaneous reactions and the read out narrative sequences.